Análise fotoelástica das próteses implantossuportadas esplintadas - Torcato, Leonardo Bueno [UNESP] (2010)
The aim of this study was to evaluate the influence of implant length on the stress distribution in 2 splinted implants with screw-retained dentures. Three models were made of photoelastic resin PL-2 with 2 implants and splinted implant supported dentures. External hex implants measuring 4.00mm in diameter and different lengths (8.5; 10 and 13 mm) were used. Model 1 - 1st Implant-8.5mm + 2nd Implant-8.5mm; Model 2 - 1st Implant-10.00mm + 2nd Implant-8.5mm; Model 3- 1st Implant-13.00mm + 2nd Implant-8.5mm. Crowns with a standard height were made of Ni-Cr alloy. Axial load of 100N and oblique (45°) load of 50N were applied by means of a universal test machine (EMIC DL 3000) at fixed and standard points on the occlusal surface. A circular polariscope was used to visualize the stress. The results were analyzed qualitatively using a graphic software. When axial load was applied the stresses were concentrated around the implant body in Models 1 and 2, and there was a better distribution when the implant length of 8.5mm (Model 1) was increased to 10mm (Model 2). However, when the 1st implant length of 8.5mm (Model 1) was increased to 13mm (Model 3), the stresses diminished significantly and were concentrated mainly on the apex of the implant. When an oblique load was applied, the stresses were concentrated on the opposite side of the load application and in the apical region; the fringes presented lower concentration as the length of the 1st implant was increased. It was concluded that: As the length of the 1st implant was increased, the intensity of stress diminished. The stress diminished significantly when the length of the first implant was increased from 8.5mm to 13mm